UPAKARA PANCA LINGGA AS SYMBOLS OF PANCA DEWATA AT HINDU RITUAL PRACTICES IN LOMBOK - Wirawan, I Wayan Ardhi; Sueca, I Nyoman; Sumari, Ni Made; Ketut Putra, I Gusti Ngurah (Widya Sandhi, 2019)
This study aims to study the upakara Panca Lingga means of ceremony as a symbol of Panca Dewata in the implementation of Hindu rituals in Lombok. This research was designed in an interpretative qualitative method using a case study model. The results of the study found that the means of ceremony panca lingga is one form of ceremonial facility which is categorized as having a uniqueness that is carried out in the implementation of rituals on the Hindu community in Lombok. The uniqueness that seems in principle is a symbolic to ask for God's grace in its manifestation as the Five Gods, namely Dewa Iswara, Dewa Brahma, Dewa Maha Dewa, Dewa Wisnu and Dewa Ã‡iwa. The Panca Dewata were requested to be present, worshiped and confirmed its place (negtegan) in the ceremony using the ceremony. Upakara Panca Lingga is very sanctified starting from the selection of the material element, which has the right to make it, the procession of its making up to the authority of the devout people, all of which are provisions that indicate the primacy of the ceremony.